On the performance of modified generalised quadrature spatial modulation under correlated Weibull fading. (20th January 2023) - Gunde, Kiran; Sundru, Anuradha
To improve the data rate of "quadrature spatial modulation (QSM)", a "modified generalised QSM (mGQSM)" scheme is developed. The mGQSM employs two sets of active antenna patterns (AAP), one for transmitting the real part of the selected data symbol and the other for transmitting the imaginary part of the same symbol. In mGQSM, the number of AAP vectors is more when compared to the generalised QSM (GQSM). This paper presents the mGQSM and "reduced codebook mGQSM (RC-mGQSM)" system performances over correlated Weibull fading channels under two different fading environments. We consider Weibull non-fading and deep-fading environments with Weibull parameter values are equal to 5 and 0.5, respectively. Using maximum likelihood (ML) detector, the mGQSM and RC-mGQSM systems are compared to QSM and GQSM systems over uncorrelated and correlated Weibull channels. Also presents the performance of the mGQSM in the existence of an imperfect channel knowledge and compared it to QSM.